Magnetic Properties, Adhesion, and Nanomechanical Property of Co40Fe40W20 Films on Si (100) Substrate. (20th July 2020) - Liu, Wen-Jen; Chang, Yung-Huang; Ou, Sin-Liang; Chen, Yuan-Tsung; Liang, You-Cheng; Huang, Bo-Jia; Chu, Chun-Lin; Chiang, Chia-Chin; Wu, Te-Ho
Abstract : In this study, a Co40 Fe40 W20 alloy was sputtered onto Si (100) with thicknesses (t f ) ranging from 18 to 90 nm, and the corresponding structure, magnetic properties, adhesive characteristics, and nanomechanical properties were investigated. X-ray diffraction (XRD) patterns of the Co40 Fe40 W20 films demonstrated a significant crystalline body-centered cubic (BCC) CoFe (110) structure when the thickness was 42 nm, and an amorphous status was shown when the thickness was 18 nm, 30 nm, 60 nm, and 90 nm. The saturation magnetization (M s ) showed a saturated trend as t f was increased. Moreover, the coercivity (H c ) showed a minimum 1.65 Oe with 30 nm. H c was smaller than 4.5 Oe owing to the small grain size distribution and amorphous structure, indicating that the Co40 Fe40 W20 film had soft magnetism. The low-frequency alternating current magnetic susceptibility (χ ac ) decreased as the frequency was increased. The χ ac revealed a thickness effect when greater thicknesses had a large χ ac . The maximum χ ac and optimal resonance frequency (f res ) of Co40 Fe40 W20 were investigated. The maximum χ ac indicated the spin sensitivity and was maximized at the optimal resonance frequency. The 90 mm thickness had the highest χ ac 0.18 value at an f res of 50 Hz. The contact angles of the Co40 Fe40 W20 films are less than 90°, which indicated that the film had a good wetting effect and hydrophilicity. The surface energy was correlated with the adhesion and displayed a concave-down trend. CoFeW films can be used as a seed or buffer layer; therefore, the surface energy and adhesion are very important. The highest surface energy was 30.12 mJ/mm 2 at 42 nm and demonstrated high adhesion. High surface energy has corresponding strong adhesive performance. The increased surface roughness can induce domain wall pinning effect and high surface energy, causing a high coercivity and strong adhesion. The increase of hardness and Young's modulus could be reasonably inferred from the thinner CoFeW films. The hardness and Young's modulus of CoFeW films are also displayed to saturated tendency when increasing thickness.